Studi Kasus Perbandingan Pengguna dan Non-Pengguna E-Commerce Pada UMKM Kerupuk Amplang Udang Di Kecamatan Keritang Kabupaten Indragiri Hilir - Rara Mulyunika; Yanti Mayasari Ginting (Jurnal Ekonomi Manajemen dan Bisnis (JEMB), 2026)
The current development of digital technology requires MSMEs to transform in order to survive and compete in an increasingly competitive market. The purpose of this study was to analyze and compare the income levels between Micro, Small, and Medium Enterprise (MSME) actors of shrimp amplang crackers who utilize e-commerce platforms and those who do not in Keritang District, Indragiri Hilir Regency. A descriptive quantitative approach was applied. The population encompassed all shrimp amplang cracker businesses in the region, with samples selected via purposive sampling, consisting of one e-commerce user and one non-e-commerce user. Primary and secondary data sources were collected through questionnaires, observations, in-depth interviews, and documentation, then analyzed using income and SWOT analysis. The results indicated that the revenue of e-commerce users was significantly higher than conventional businesses. Based on the SWOT analysis, both MSMEs are located in quadrant I, recommending an aggressive strategy by optimizing SO (strengths-opportunities) strategies. In conclusion, the adoption of e-commerce technology is proven to effectively boost sales turnover and expand market reach, implying the critical importance of accelerating digitization for local MSMEs to enhance their economic welfare.